Identifying the components o f social responsibility in the curriculum of the skill university - maryam Talebian-darzi; Vahid Fallah; mohammad salehi (Shahid Chamran University of Ahvaz, 2021)
Identifying Components of Social Responsibility in Curriculum of Skills UniversityIntroductionPlaying the role of an active citizen in civil society is possible by augmenting the sense of social responsibility in the community. Therefore, to achieve this goal, teaching the principles, methods and approaches of social responsibility should be reflected in the curriculum. The goal of this report is to identify the components of social responsibility in the curriculum of Skills University as one of the top universities for creating sustainable employment.MethodsA qualitative method was used in this study according to the purpose and nature of research. Statistical sample includes 18 experts in the field of skills training; Sampling was performed purposefully. Data collection tools are semi-constructive interviews and data analysis methods based on thematic analysis technique. Findings from the study showed that educational content, learning and teaching activities, and continuous evaluations are principles that, in terms of social responsibility, lead higher education curricula toward skill-oriented curricula. The connection between the components and elements of the curriculum as an educational sub-system and macro-educational programs can make the social institution of higher education more capable.ResultsThe results showed that the three main categories of educational content, learning and teaching activities, and continuous assessment are social responsibility categories in the curriculum of Skills University. Based on these categories, a model of social responsibility was developed in the curriculum of Skills University.DiscussionAchieving social responsibility requires that Skill University change the curriculum paradigm and the elements contained in it to institutionalize the components of social responsibility in the core of curriculum activities. The establishment of a social responsibility research center in Skills University and affiliated colleges to monitor the curriculum contexts, behaviors and structures according to the components identified in this study can be considered a turning point for this goal. Keywords: Curriculum, Skills University, Social Responsibility